PROFIL KETERAMPILAN BERTANYA SISWA PADA PEMBELAJARAN IPA - Requistiawati Requistiawati; Tri Jalmo; Berti Yolida (Universitas Lampung, 2017)
The purpose of this study was to describe the students questioning skill and quality of male and female students question based on Bloom's taxonomy revision. This study design using simple descriptive design. The samples were selected by simple random sampling technique that were class VII-1, VII-2, VII-3, VIII-1, VIII-3 and VIII-4 junior high school. The data in were qualitative data that were the questioning skill and quality of male and female students question. The accumulation data technique used observation and questionnaire. The data were obtained from percentage with descriptive analysis. The results of this study indicate that the questioning skill of students classified in